ROLE AND PROBLEMS STATE IN INCREASING OF EFFICIENCY OF THE DEVELOPMENT AND MANAGEMENT MARKET TO PREMISES - R. M. Dullueva; T. S. Izieva; M. N. Isalova (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
In article are considered main system problems, holding up development market to premises, removal which without government regulation running on him processes practically impossible. The certain primary tasks of the government regulation market to premises and offered different ways their efficient decision. It is shown that for efficient management behavior different subject on the market of the premises state is in the first place required provide his observability, predictability and controllability.